The Morphometry of the Deep-Water Sinuous Mendocino Channel and the Immediate Environs, Northeastern Pacific Ocean - James V. Gardner (Geosciences, 2017)
Mendocino Channel, a deep-water sinuous channel located along the base of Gorda Escarpment, was for the first time completely mapped with a multibeam echosounder. This study uses newly acquired multibeam bathymetry and backscatter, together with supporting multichannel seismic and sediment core data to quantitatively describe the morphometry of the entire Mendocino Channel and to explore the age and possible causes that may have contributed to the formation and maintenance of the channel. The first 42 km of the channel is a linear reach followed for the next 83.8 km by a sinuous reach. The sinuous reach has a sinuosity index of 1.66 before it changes back to a linear reach for the next 22.2 km. A second sinuous reach is 40.2 km long and the two reaches are separated by a crevasse splay and a large landslide that deflected the channel northwest towards Gorda Basin. Both sinuous reaches have oxbow bends, cut-off meanders, interior and exterior terraces and extensive levee systems. The lower sinuous reach becomes more linear for the next 22.2 km before the channel relief falls below the resolution of the data. Levees suddenly decrease in height above the channel floor mid-way along the lower linear reach close to where the channel makes a 90° turn to the southwest. The entire channel floor is smooth at the resolution of the data and only two large mounds and one large sediment pile were found on the channel floor. The bathymetry and acoustic backscatter, together with previously collected seismic data and box and piston cores provide details to suggest Mendocino Channel may be no older than early Quaternary. A combination of significant and numerous earthquakes and wave-loading resuspension by storms are the most likely processes that generated turbidity currents that have formed and modified Mendocino Channel.